Cortical Activation during Landmark-Centered vs. Gaze-Centered Memory of Saccade Targets in the Human: An FMRI Study - Chen, Ying; Crawford, J. D. (Frontiers in Systems Neuroscience, 2017)
A remembered saccade target could be encoded in egocentric coordinates such as gaze-centered, or relative to some external allocentric landmark that is independent of the target or gaze (landmark-centered). In comparison to egocentric mechanisms, very little is known about such a landmark-centered representation. Here, we used an event-related fMRI design to identify brain areas supporting these two types of spatial coding (i.e., landmark-centered vs. gaze-centered) for target memory during the Delay phase where only target location, not saccade direction, was specified. The paradigm included three tasks with identical display of visual stimuli but different auditory instructions: Landmark Saccade (remember target location relative to a visual landmark, independent of gaze), Control Saccade (remember original target location relative to gaze fixation, independent of the landmark), and a non-spatial control, Color Report (report target color). During the Delay phase, the Control and Landmark Saccade tasks activated overlapping areas in posterior parietal cortex (PPC) and frontal cortex as compared to the color control, but with higher activation in PPC for target coding in the Control Saccade task and higher activation in temporal and occipital cortex for target coding in Landmark Saccade task. Gaze-centered directional selectivity was observed in superior occipital gyrus and inferior occipital gyrus, whereas landmark-centered directional selectivity was observed in precuneus and midposterior intraparietal sulcus. During the Response phase after saccade direction was specified, the parietofrontal network in the left hemisphere showed higher activation for rightward than leftward saccades. Our results suggest that cortical activation for coding saccade target direction relative to a visual landmark differ from gaze-centered directional selectivity for target memory, from the mechanisms for other types of allocentric tasks, and from the directionally selective mechanisms for saccade planning and execution.